Venture capital and investor readiness in a post-crisis and state-rescaling context: Revisiting the North East of England. (June 2015) - Wray, Felicity
This paper supplies a historical and geographically rooted account of how three separate but ongoing processes (state-rescaling, recessionary conditions and SME business support reforms) were perceived to be intersecting and manifesting themselves at the juncture of venture capital and investment readiness provision in the North East of England primarily from the perspective of local fund managers in December 2012. The paper demonstrates how these myriad processes played out in both predictable and unusual ways in a region often constructed as lagging and not known for its buoyant levels of venture capital activity. In particular, the paper provides empirical insights into the uncertainties created by the Coalition government during the transition from Regional Development Agencies to Local Enterprise Partnerships while also going beyond investor narratives to highlight how the empirical findings connect to broader debates in local and regional development. Here the way in which venture capital policy speaks to the Coalition aspirations of rebalancing the economy, decentralisation and localism in both complementary and contradictory ways are emphasised. As is how the North East (but also other Northern regions) is embedded in multi-scalar relationships by virtue of its connections to EU funding streams, and in particular equity funding through the JEREMIE programme, thus raising interesting questions about the future direction of UK venture capital policy.